The emergence of the additional language teacher/ adviser under the complexity paradigm - Borges, Elaine Ferreira do Vale; Silva, Walkyria Magno e (DELTA: Documentação e Estudos em Linguística Teórica e Aplicada, 2019)
In this text, we discuss the emergence of a complex additional language teacher/adviser under the complexity theory framework by reﬂecting upon disturbances in the teaching and learning subsystems of pre-service education. The complex teacher/adviser values all sub- and suprasystems, embraces the fractalized identities, conciliates assorted conceptions associated to this role, energizes and moves different systems linked to the profession, and uses several methods and approaches to language teaching and learning. We bring up some evidences of the complex teacher/ adviser emergence in language teaching preparation and in language learning advising.